Kepuasan Kerja sebagai Variabel Intervening Pada Pengaruh Work-Life Balance dan Stres Kerja Terhadap Turnover Intention - Muhammad Andi Prayogi; Murviana Koto; Muhammad Arif (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
This study aims to prove the effect of Work-Life Balance and work stress on turnover intention mediated by job satisfaction of Bank Syariah Account Officers in Medan. The location of this research is in the city of Medan with the subject of research is the Sharia Bank in the city of Medan, the population of this study amounted to 150 Account Officers, with sampling techniques using Probability Sampling with simple random sampling techniques, determining the sample using the Slovin formula. Data analysis techniques in this study used path analysis. The research results partially showed that Work-life balance and work stress had a positive and significant effect on job satisfaction, Work-life balance and work stress had a positive and significant effect on turnover intention, job satisfaction had a negative and significant effect on turnover intention. Work-life balance directly influences turnover intention without going through job satisfaction, job satisfaction is not an intervening variable, Job stress has a direct effect on turnover intention without going through job satisfaction, job satisfaction is not an intervening variable.